Instantly Hooked? Freebies and Samples of Opioids, Cannabis, MDMA, and Other Drugs in an Illicit E-Commerce Market. (April 2018) - Ladegaard, Isak
Do drug dealers entice nonusers with free samples? Police, the popular press, and social media users say so, but crime researchers have found little support for this theory and argue instead that sample distribution is an unsound strategy for illegal market business. But what about in digital drug markets, where operational logics are based on sophisticated anonymization technology and reputation systems? The author collected data from a large e-commerce website for drugs over 305 days in 2014 and 2015 and documents that (a) drug dealers give away samples of all major substance categories and (b) sample distribution increases vendor sales for prescription drugs and opioid-based painkillers. To explore possible explanations of these findings, the author collected data from the market's online forum and analyzed 175 discussions (2, 218 posts) about samples. Among the findings is that samples are preferably given to reputable review writers, or "drug critics."